What do breastfeeding women taking herbal galactagogues perceive of community pharmacists’ role in breastfeeding support? A qualitative study - Sim, Tin Fei; Hattingh, Laetitia; Sherriff, Jill; Tee, Lisa (MDPI AG, 2015)
Information from pharmacists may affect breastfeeding womens’ decisions and choice of therapy. Community pharmacies remain one of the main sources of herbal medicines in Australia. In this study, we aimed to explore the perspectives of breastfeeding women on pharmacists’ role and whether there is potential for role expansion, as well as the facilitators and barriers in meeting their healthcare-related needs in the community pharmacy setting. Semi-structured in-depth interviews were conducted with 20 Western Australian women who were using one or more herbal galactagogues while breastfeeding. Participants’ views were classified into three major themes: (i) facilitators and (ii) barriers to an increased role of pharmacists; and (iii) implementation of breastfeeding related-services in community pharmacy settings. Overall perspectives of participants were positive about the potential for role expansion of pharmacists to meet their breastfeeding-related needs. Whilst most participants perceived community pharmacies as convenient sources of trusted information, some recognised barriers to an increased role of pharmacists. Several breastfeeding support services perceived to be useful in community pharmacy settings were identified. Issues raised highlighted areas of pharmacy practice which required improvement and revealed opportunities for expansion of pharmacists’ role to better support women and promote breastfeeding in the community.